Examining the civil society organisations support as a requisite for desirable administrative reform outcomes: evidence from Nigerian power industry / Ashiru Olayemi … [et al.] - Olayemi, Ashiru; x, Aliyu; Singaravelloo, Kuppusamy; Mansor, Norma (Universiti Teknologi MARA, 2021)
Administrative reform has long been recognised as an integral part of public sector management aimed at improving the service delivery capacity of public sector organisation. Reform initiative had been conducted by the successive government from post-independent until this contemporary period. However, these giants' strides made by the government in Nigeria to repositioning the power industry have often been disappointing. That is, no considerable progress achieved; the reform has overtime produced undesirable outcomes. Put simply, there exists a big gap between reform expectation and the actual outcome. Thus, this study investigates the influence of civil society organisation support to reform initiative as requisite for positive outcomes. The paper adopted a survey research method; a cross-section approach and a purposive sampling technique. In all, 463 closed-ended questionnaires were distributed to electricity subscribers and 401 returned. WarpPLS "structural equation model" software tools of analysis suitable for nonlinear data were employed to analyse the data obtained. The study found an absence of synergy between civil society and government which is critical to purposeful and desirable reform outcomes, and when absence the reform is unlikely to the successful. Therefore, the study recommends active participation of civil society organisation as key stakeholders in the reform process to facilitates result-driven administrative reform outcome.